Effects of chronic cold-water immersion in elite rugby players - Tavares, F.; Beaven, M.; Teles, J.; Baker, D.; Healey, P.; Smith, T. B.; Driller, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Although the acute effects of cold-water immersion (CWI) have been widely investigated, research analyzing the effects of CWI over a chronic period in highly trained athletes is scarce. The aim of this study was to investigate the effects of CWI during an intense 3-wk preseason phase in elite rugby athletes. Methods: A total of 23 elite male rugby union athletes were randomized to either CWI (10 min at 10°C, n=10) or a passive recovery control (CON, n = 13) during 3 wk of high-volume training. Athletes were exposed to either CWI or CON after each training day (12 d in total). Running loads, conditioning, and gym sessions were kept the same between groups. Measures of countermovement jump, perceived muscle soreness, and wellness were obtained twice a week, and saliva samples for determining cortisol and interleukin-6 were collected once per week. Results: Although no significant differences were observed between CWI and CON for any measure, CWI resulted in lower fatigue markers throughout the study as demonstrated by the moderate effects on muscle soreness (d=0.58-0.91) and interleukin-6 (d = -0.83) and the small effects (d = 0.23-0.38) on countermovement jump in comparison with CON. Conclusions: CWI may provide some beneficial effect by reducing fatigue and soreness during an intense 3-wk training phase in elite rugby athletes.